Effects of Aerobic Training Progression on Blood Pressure in Individuals With Hypertension: A Systematic Review With Meta-Analysis and Meta-Regression - de Barcelos, Guilherme Tadeu; Heberle, Isabel; Coneglian, Juliana Cavestré; Vieira, Bruno Allan; Delevatti, Rodrigo Sudatti; Gerage, Aline Mendes (Frontiers in Sports and Active Living, 2022)
Introduction: Aerobic training of moderate intensity is the primary modality recommended in the management of hypertension. The manipulation of training variables can be an important strategy for the continuity of health benefits; however, little is known about the effects of the progression of aerobic training variables in the adaptations of blood pressure in hypertensive adults. Objective: To analyze, through a systematic review with meta-analysis, the effects of aerobic training with and without progression on systolic blood pressure (SBP) and diastolic blood pressure (DBP) in hypertensive adults. Method: The search for the studies was carried out in the PubMed, Cochrane Central, SPORTDiscus and LILACS databases. Clinical trials that analyzed the effect of aerobic training, lasting at least six weeks, on blood pressure in hypertensive individuals comparing with a control group without intervention were selected. The selection of studies and data extraction were carried out independently by two pairs of researchers. The results are presented as mean difference and 95% confidence interval. Statistical significance was considered with p <0.05. Results: Of the 13028 studies found, 24 were selected and included in this review, 12 with progression of training variables and 12 without progression, with a total of 1207 participants analyzed. There was a reduction in SBP after aerobic training with progression (-10.67 mmHg; 95% CI -15.421, -5.926; p <0.001) and without progression (-10.17 mmHg; CI -12.213, -8.120; p <0.001). DBP also decreased after aerobic training with progression (-5.49 mmHg; 95% CI -8.663, -2.310; p <0.001) and without progression (-6.51 mmHg; 95% CI -9.147, -3.868; p < 0.001). According to the results of the meta-regression analyses, only age showed an association with the reduction of SBP (β: -0.323; CI -0.339, -0.307; p <0.001). Conclusion: Aerobic training promotes a reduction in the SBP and DBP levels of adults with hypertension, regardless of whether or not the training variables progression.